Deep Learning Approach In Islamic Religious Education - Purnomo Agung; Rika Sa’diyah (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study aims to analyze the deep learning approach in the context of Islamic Religious Education (PAI) in the digital era. Deep learning, as part of the 21st-century educational paradigm, emphasizes the active involvement of students in building meaningful understanding, critical thinking, and transferring knowledge into real-life contexts. This study used a systematic literature review (SLR) method on 28 national journal articles published between 2016 and 2026. The results show that the deep learning approach can significantly improve the quality of PAI learning, including: (1) increasing the holistic understanding of religious concepts, (2) developing students' character and morals, (3) integrating Islamic values ​​in solving contextual problems, and (4) increasing student motivation and engagement. The findings also identify factors inhibiting implementation, including the limited pedagogical competence of PAI teachers and the minimal digital infrastructure support in Islamic-based schools. This study concludes that the integration of deep learning in PAI requires curriculum reorientation, increased teacher capacity, and consistent policy support from educational stakeholders.